A Fuzzy Logic-Based Video Subtitle and Caption Coloring System. (22nd April 2012) - Davoudi, Mohsen; Menhaj, M. B.; Seif Naraghi, Nima; Aref, Ali; Davoodi, Majid; Davoudi, Mehdi
Abstract : An approach has been proposed for automatic adaptive subtitle coloring using fuzzy logic-based algorithm. This system changes the color of the video subtitle/caption to "pleasant" color according to color harmony and the visual perception of the image background colors. In the fuzzy analyzer unit, using RGB histograms of background image, the R, G, and B values for the color of the subtitle/caption are computed using fixed fuzzy IF-THEN rules fully driven from the color harmony theories to satisfy complementary color and subtitle-background color harmony conditions. A real-time hardware structure has been proposed for implementation of the front-end processing unit as well as the fuzzy analyzer unit.